Ethical Aspects of Communication in the Academic Environment - Helena Grecmanova; Miroslav Dopita; Eva Urbanovska (Communications - Scientific letters of the University of Zilina, 2017)
The changes in the academic environment are related to the changes in the organisational culture and subsequently also in communication at universities. Transformation of universities from temples of knowledge into organisations producing qualified workforce and research findings applicable in practice is very important in this process. Changes in the relations and communication among academic staff as well as between the management of universities and their employees are connected with this process too. The presented paper focuses on these relations and communication among academics and between academics and the management of universities in detail. The method of secondary analysis of data collected by means of an organizational climate questionnaire at a teacher training faculty was applied in the article. The analysis of the mentioned data illustrates perception of the management’s communication by the academic staff.